2017
DOI: 10.1007/s10616-017-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

A new method to evaluate anti-allergic effect of food component by measuring leukotriene B4 from a mouse mast cell line

Abstract: Leukotrienes (LTs), chemical mediators produced by mast cells, play an important role in allergic symptoms such as food allergies and hay fever. We tried to construct an evaluation method for the anti-LTB activity of chemical substances using a mast cell line, PB-3c. PB-3c pre-cultured with or without arachidonic acid (AA) was stimulated by calcium ionophore (A23187) for 20 min, and LTB production by the cells was determined by HPLC with UV detection. LTB was not detected when PB-3c was pre-cultured without AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Quercetin can be found in red wine, apples, green tea and onion and contains both anti-inflammatory and anti-oxidative properties (69). It has been reported to inhibit leukotriene B4 levels in MCs (70), reduce the gene expression of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-8) (71) and suppress inflammation in IgE-mediated intestinal epithelial cell (Caco-2) and rat basophil (RBL-2H3) activation models (72). Flavonoids have also been shown to inhibit allergic effector cells such as MCs known to contribute to allergic symptoms (73).…”
Section: Combining Lcpufas To Prevent Lipid Peroxidationmentioning
confidence: 99%
“…Quercetin can be found in red wine, apples, green tea and onion and contains both anti-inflammatory and anti-oxidative properties (69). It has been reported to inhibit leukotriene B4 levels in MCs (70), reduce the gene expression of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-8) (71) and suppress inflammation in IgE-mediated intestinal epithelial cell (Caco-2) and rat basophil (RBL-2H3) activation models (72). Flavonoids have also been shown to inhibit allergic effector cells such as MCs known to contribute to allergic symptoms (73).…”
Section: Combining Lcpufas To Prevent Lipid Peroxidationmentioning
confidence: 99%
“…Genistein is a non-steroidal polyphenol that possesses diverse pharmacological activities. There is evidence for the protective effects of Genistein in inflammation [21][22][23], diabetes [24,25], cancer [26,27] and hypersensitivity reactions [28,29]. In a recent paper, Kim, Dong Hwan et al reported the anti-inflammatory activity of Genistein on mast cells via inhibiting cytokines and the ERK pathway and proposed potential of Genistein for the treatment of allergic inflammation and anaphylactic shock [30].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin also targeted LTC 4 biosynthesis in mast cells by blocking 5-LOX translocation and cPLA 2 activation [ 102 ]. Quercetin reduced biosynthesis of LTB 4 in RBL-1 basophils, neutrophils, and murine PB-3c mast cells [ 146 , 147 , 148 ], while genistein acted on eosinophils decreasing LTC 4 synthesis via inhibition of 5-LOX translocation [ 95 ]. Likewise, the effect of silibinin on macrophages (Kupffer cells) was associated with lower LTB 4 levels while sparing the COX-2 pathway [ 149 , 150 ].…”
Section: Resultsmentioning
confidence: 99%